Marketing Strategy in Online Books Sales - Prayoga, Inggar; Oktafiani, Dina (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The objective of this research is to explain the online book sales system and its sales cycle. The method used in this research was the descriptive method by observing and interviewing to obtain information related to the investigation, such as the types of books sold, prices and business processes. The results of this research showed that by implementing an online bookstore, it can increase revenue, the number of customers, expanding the business reach of the company and means of promotion. The conclusion obtained in this research was online book sales are the best solution to develop a book sales business and make it easier for consumers to get the information and transaction, both saving time and more affordable.